Olexandr Oleksiyovych Kostrub - Ukrainian Association of Orthopedic Traumatologists, - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 70th anniversary of the birth of the Honored Doctor of Ukraine, head of the department of sports and ballet trauma at the Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine, Doctor of Medical Sciences, Professor Kostrub O. O.